Walls and fortresses: borderscapes and the cinematic imaginary - Mendes, Ana Cristina (2017)
In tandem with a postnational imaginary nurtured by an ever-present promise of deterritorialized mobility and burgeoning migratory fluxes, walls and fences separating nation states multiply. This is a burning issue: even though nation states at the centre of the global order increasingly present themselves as postnational, calls for tighter border security (prompted by traumatic events such as the London Underground bombings, the riots in Paris’s banlieues, the September 11 attacks and the massive number of refugees and migrants drowning in the Mediterranean and being hit by trains after stepping over fences to enter in the Eurotunnel area, in Calais) undermine utopian notions of both a borderless New Europe and the USA as the Promised Land. This editorial of Transnational Cinemas introduces the special issue ‘Walls and fortresses: borderscapes and the cinematic imaginary’, which includes essays focusing on the interrelated motifs of borderscapes as they are represented in transnational cinematographies, from Palestine to Sweden, Spain, Finland and France, and as constituting premises of cinematic production. Through this critical movement, this special issue analyses the ways various cinematic practices, technologies and crossmedia developments impact questions of perception, experience and representation of borderscapes.